Kontribusi Pelaksanaan MBKM terhadap Kemandirian dan Kesiapan Mahasiswa Menghadapi Dunia Kerja - Junarti Junarti; Ari Indriani; Novi Mayasari (Jurnal Pendidikan Edutama, 2023)
Abstract: The purpose of this research is to explore the profile of learning independence and student readiness in facing the world of work which is built through MBKM activities and to describe the effect of learning independent on student readiness in facing the world of work through MBKM activities. The research method used is descriptive quantitative using a survey method to obtain data through a self-sufficiency and readiness questionnaire. The population is from students who have been subject to MBKM activities, namely as many as 365 students. The sample was selected by purposive sampling technique based on the number of students who filled out the questionnaire, namely as many as 107 people, then the number of samples was selected based on the students who took part in the MBKM as many as 47 people. Data analysis used a quantitative descriptive test and regression test. The results of the study, that the profile of learning independence and the readiness of students to face the world of work who took MBKM had a better average score than those who did not take MBKM but the difference was less significant. The level of learning independence and readiness was dominated by the medium category of 55.32% and 72.34% of 47 students. There is an influence of independent learning on student readiness in facing the world of work of 24.6%, while 75.04% is influenced by other factors. Abstrak: Tujuan penelitian ini yaitu untuk menggali profil kemandirian belajar dan kesiapan mahasiswa dalam menghadapi dunia kerja yang dibangun melalui kegiatan MBKM dan untuk mendeskripsikan pengaruh kemandirian belajar terhadap kesiapan mahasiswa dalam menghadapi dunia kerja dengan melalui kegiatan MBKM. Metode penelitian yang digunakan deskriptif kuantitatif dengan menggunakan metode survei untuk mendapatkan data melalui angket kemandirian dan kesiapan. Populasinya dari mahasiswa yang sudah dikenai kegiatan MBKM yakni sebanyak 365 mahasiswa. Sampel dipilih dengan teknik purposive sampling berdasarkan jumlah mahasiswa yang mengisi angket yakni sebanyak 107 orang, kemudian jumlah sampel dipilih berdasarkan mahasiswa yang  mengikuti MBKM sebanyak 47 orang. Analisis data menggunakan uji deskriptif kuantitatif dan uji regresi. Hasil penelitian, bahwa profil kemandirian belajar  dan kesiapan mahasiswa menghadapi dunia kerja yang mengikuti MBKM nilai rata-rata lebih baik dengan yang tidak mengikuti MBKM namun perbedaannya kurang signifikan. Tingkat kemandirian belajar dan kesiapan  didominasi pada kategori sedang sebesar 55,32%  dan 72,34% dari 47 mahasiswa. Terdapat pengaruh kemandirian belajar terhadap kesiapan mahasiswa dalam menghadapi dunia kerja sebesar 24,6%, sedangkan 75,04% dipengaruhi oleh faktor